Digital humanities in US academic libraries: case studies - Kelda Habing; Lian Ruan (Digital Transformation and Society)
Purpose – Digital Humanities is a robust area of research and practice at universities and their libraries across the world. This case study investigates the unique DH practices of seven US academic libraries to provide insights into how varied academic libraries operate their DH programs. Design/methodology/approach – Semi-structured interviews with nine library staff in DH or DH-adjacent positions at seven US academic libraries were used to investigate library DH practices. Findings – This case study highlighted key areas of academic library DH practices including Space, Technology, Staff, Instruction and Collaboration. Practices in these areas were compared against each other and literature to comment on the current state of DH library practices and offer some recommendations for select areas. Research limitations/implications – This case study interviewed staff in a limited number of US libraries and is not generalizable to or a reflection of the many academic libraries in the US or across the world. Originality/value – The juxtaposition of multiple libraries’ DH activities provides a unique perspective on academic library DH practice, as many studies investigate only a single library as their subject.